Implementasi Metode Triple Exponential Smoothing Berbasis Website Dalam Memprediksi Persediaan Barang Pada Chronix Project - Hendi Setiawan; Dias Erlangga Valdiviano (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2023)
Chronix project is a company engaged in Convection. One of its main tasks is to manage the inventory of goods for the daily needs of the store, because these goods cannot last for a long time, so if the receipt of too many goods will have an impact on the quality of these goods, if too little acceptance will cause losses to the store and also to the level of consumer confidence in the store. Forecasting in the ordering of goods generally uses the Triple Exponential Smoothing method, which is an average method that gives greater weight to the latest demand and is more reliable for analyzing data that shows a trend.